2020
DOI: 10.1021/acsami.9b19956
|View full text |Cite
|
Sign up to set email alerts
|

Following in Situ the Degradation of Mesoporous Silica in Biorelevant Conditions: At Last, a Good Comprehension of the Structure Influence

Abstract: Mesoporous silica nanoparticles (MSNs) have seen a fast development as drug delivery carriers thanks to their tunable porosity and high loading capacity. The employ of MSNs in biomedical applications requires a good understanding of their degradation behavior both to control drug release and to assess possible toxicity issues on human health. In this work, we study mesoporous silica degradation in biologically relevant conditions through in situ ellipsometry on model mesoporous nanoparticle or continuous thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 66 publications
1
35
1
Order By: Relevance
“…While titania thin films exhibit high chemical stability in biologically relevant conditions, silica thin films in aqueous environment are hydrolyzed and form silicilic acid or silicate species [ 19 ]. This progressive dissolution of the silica matrix promotes the release not only of the carried drug, but also of solubilized silica which might nucleate and accumulate randomly, posing a toxicity risk to the organism [ 81 , 92 ].…”
Section: Functional Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…While titania thin films exhibit high chemical stability in biologically relevant conditions, silica thin films in aqueous environment are hydrolyzed and form silicilic acid or silicate species [ 19 ]. This progressive dissolution of the silica matrix promotes the release not only of the carried drug, but also of solubilized silica which might nucleate and accumulate randomly, posing a toxicity risk to the organism [ 81 , 92 ].…”
Section: Functional Groupsmentioning
confidence: 99%
“…Despite the fact that silica substrates undergo biodegradation in in-vivo conditions due to the solubilization of silica matrix and the consequent formation of silicilic acid [ 19 , 101 ], studies have shown that they can be efficiently sterilized and still be used as bioactive coatings, having the advantage of being a source of ions necessary for cell differentiation if submerged in a solution containing inorganic ions similar to body fluid [ 17 ]. For instance, Chai and coworkers [ 88 ] used SiO 2 mesoporous thin films as support for osteoblast-like cell growth.…”
Section: Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the aminosilane will reduce the dissolution rate of the silica thanks to a combination of factors including the inductive donor effect of the alkyl chain reducing the electropositive character of Si centre, and an increase in hydrophobicity. 42,43 In other cases, the presence of aminosilane has been reported to increase the dissolution rate of the silica, possibly due to the presence of amine groups catalysing the hydrolysis as well as the decrease of the condensation of the silica network. 29,39 For these reason and because the fluo-rescence increase remains small (increase of 15% at best), we decided to use only an excess of 10 equivalent of APTMS per dye.…”
Section: Dye Loading In the Silica Matrixmentioning
confidence: 99%
“…[ 44,45 ] In fact, one of the main parameters controlling the degradation kinetics of mesoporous silica is its surface area. [ 32,45,46 ] In addition, pH and temperature also greatly affect silica dissolution. [ 47,48 ] The different parameters involved in silica dissolution lead to a huge variety of possible scenarios and to inconsistent results for the kinetics of silica degradation in physiological buffers or biological media.…”
Section: Introductionmentioning
confidence: 99%